Investigation of stiffness and damping coefficients in fluid film bearing with bio-oils and mineral-based oil. (November 2022) - Sadiq, Muhammad Imran; Ghopa, Wan Aizon W.; Nuawi, Mohd. Zaki; Rasani, Mohammad Rasidi; Khamis, Nor Kamaliana; Mansor, Mohd Radzi Abu
Abstract: Rotating machinery utilizes fluid film bearings because of their good load carrying capacity and inherent damping properties. Fluid film bearings offer stiffness and damping parameters to ensure dynamic stability. The damping and stiffness characteristics of oil film significantly change the critical speed and unbalance response of the rotor. The damping and stiffness coefficients (direct, cross-coupled) may lead to system instability, also known as self-excited vibrations. Bio-oils have good tribological and physiochemical properties. They are also environment-friendly and bio-degradable. In this work, bio-oils (rapeseed, palm olein, and soybean) are evaluated in terms of their dynamic characteristics to that of mineral-based SAE40 lubricant for journal-bearing applications. The analytical extraction of damping and stiffness coefficients is performed based on the experimental dynamic viscosity data at different temperatures. In comparison to SAE40, the bio-oils have shown improved responsiveness. Bio-oils showed lower cross-coupled stiffness coefficients than SAE40, the primary source of rotor instability. The main contribution of this study is that it provides damping and stiffness coefficients for various bio-oils at different eccentricity ratios and viscosities for different types of oils. This may be used to characterize the dynamic properties of the fluid film bearing under various operating circumstances. It is concluded that the difference in cross-coupled stiffness favors bio-oils. Whereas, the difference in cross-coupled damping favors SAE40 by around 6%. This discrepancy is decreased to less than 2% for all oil's final eccentricity ratio values (bio-oils and SAE40).